Awareness among health visitors of the association between postnatal depression and intimate partner abuse. (2nd November 2020) - Davies, Emma; Spargo, Dwynwen
Abstract : Intimate partner abuse and postnatal depression (PND) are of particular significance to specialist community public health nurses in the field of health visiting practice as they are key contributors to the health and development of children. However, evidence regarding the association between these two phenomena is limited. A literature review was conducted to identify ways in which health visiting practice could be informed to identify and support women experiencing intimate partner abuse and PND. The review identified three main themes: a significant co-concurrence between intimate partner abuse and PND; a relationship between lifetime abuse and PND; and the impact of emotional abuse in relation to PND.